Fibronectin Attachment Protein Is Necessary for Efficient Attachment and Invasion of Epithelial Cells by Mycobacterium avium subsp. paratuberculosis - Secott, T. E. (American Society for Microbiology, 2002)

(untitled)
Attachment and ingestion of Mycobacterium avium subsp. paratuberculosis by two epithelial cell lines were enhanced by soluble fibronectin (FN). Peptide blocking of the FN attachment protein (FAP-P) inhibited the internalization of M. avium subsp. paratuberculosis. Disruption of FAP-P expression significantly reduced attachment and ingestion of M. avium subsp. paratuberculosis by T-24 and Caco-2 cells. The results indicate that the interaction between FN and FAP-P facilitates attachment and internalization of M. avium subsp. paratuberculosis by epithelial cells.